Laser induced self-N-doped porous graphene as an electrochemical biosensor for femtomolar miRNA detection. (15th August 2020) - Wan, Zhengfen; Umer, Muhammad; Lobino, Mirko; Thiel, David; Nguyen, Nam-Trung; Trinchi, Adrian; Shiddiky, Muhammad J.A.; Gao, Yongsheng; Li, Qin
Abstract: We report a sensitive, yet low-cost biosensor based on laser induced graphene for femtomolar microRNA (miRNA) detection. Combined with the miRNA extraction and magnetic isolation process, the target miRNAs were purified for further detection using laser induced graphene sensor. The laser induced graphene was prepared by direct laser writing on commercial polyimide (PI) and patterned via a computer-aided design system as an electrode for electrochemical biosensing. We found that the laser reduction of PI resulted in nitrogen-doped porous graphene, not only improving its conductivity but also its sensitivity to nucleic acids. Preeclampsia specific miRNA hsa-miR-486-5p was magnetically purified and directly adsorbed on the surface of graphene electrode via graphene-miRNA affinity interaction. Surface attached miRNAs were then electrochemically quantified using [Fe(CN)6 ] 3-/4- redox system. Our assay demonstrates detection of miRNA has-miR-486-5p up to concentrations as low as 10 fM with excellent reproducibility. Owing to its facile fabrication, low cost and high performance, the laser induced N-doped graphene biosensor presented here shows great potential for applications in detecting miRNA in biomedical applications. Graphical abstract: Image 1